Intense solar radiation constrains plant species richness in global grasslands - Spohn, Marie (2026)
The search for predictors of plant diversity has challenged scientists for decades. Here we identify intense photosynthetically active radiation (PAR) as a major factor constraining plant species richness in global grasslands. We show that the strength of the negative relationship between species richness and PAR increases with increasing elevation and that species richness is more strongly correlated with intense PAR than with UV-B radiation, climate variables, and atmospheric nitrogen deposition. In addition to species richness, plant biomass was also negatively correlated with PAR at higher elevations, indicating that intense PAR also constrains plant biomass in montane grasslands. Furthermore, we show that the decrease in plant species richness with increasing PAR is mainly caused by a decrease in species richness of forbs, sedges, and rushes. In contrast, species richness of grasses was only negatively correlated with PAR at high elevations, and species richness of legumes was not significantly correlated with PAR. Our results suggest that PAR constrains plant species richness in global grasslands and limits the extent to which plant species of specific functional groups can migrate uphill in response to climate warming.